Follow‐up of late‐onset Pompe disease patients with muscle magnetic resonance imaging reveals increase in fat replacement in skeletal muscles. Issue 4 (4th March 2020) - Nuñez‐Peralta, Claudia; Alonso‐Pérez, Jorge; Llauger, Jaume; Segovia, Sonia; Montesinos, Paula; Belmonte, Izaskun; Pedrosa, Irene; Montiel, Elena; Alonso‐Jiménez, Alicia; Sánchez‐González, Javier; Martínez‐Noguera, Antonio; Illa, Isabel; et al.
Abstract: Background: Late‐onset Pompe disease (LOPD) is a genetic disorder characterized by progressive degeneration of the skeletal muscles produced by a deficiency of the enzyme acid alpha‐glucosidase. Enzymatic replacement therapy with recombinant human alpha‐glucosidase seems to reduce the progression of the disease; although at the moment, it is not completely clear to what extent. Quantitative muscle magnetic resonance imaging (qMRI) is a good biomarker for the follow‐up of fat replacement in neuromuscular disorders. The aim of this study was to describe the changes observed in fat replacement in skeletal muscles using qMRI in a cohort of LOPD patients followed prospectively. Methods: A total of 36 LOPD patients were seen once every year for 4 years. qMRI, several muscle function tests, spirometry, activities of daily living scales, and quality‐of‐life scales were performed on each visit. Muscle MRI consisted of two‐point Dixon studies of the trunk and thigh muscles. Computer analysis of the images provided the percentage of muscle degenerated and replaced by fat in every muscle (known as fat fraction). Longitudinal analysis of the measures was performed using linear mixed models applying the Greenhouse–Geisser test. Results: We detected a statistically significant and continuous increase in mean thigh fat fraction both in treated (+5.8% in 3 years) and in pre‐symptomatic patients (+2.6% in 3years) (Greenhouse–Geisser p < 0.05). As an average, fat fraction increased by 1.9% per year in treated patients, compared with 0.8% in pre‐symptomatic patients. Fat fraction significantly increased in every muscle of the thighs. We observed a significant correlation between changes observed in fat fraction in qMRI and changes observed in the results of the muscle function tests performed. Moreover, we identified that muscle performance and mean thigh fat fraction at baseline visit were independent parameters influencing fat fraction progression over 4 years (analysis of covariance, p < 0.05). Conclusions: Our study identifies that skeletal muscle fat fraction continues to increase in patients with LOPD despite the treatment with enzymatic replacement therapy. These results suggest that the process of muscle degeneration is not stopped by the treatment and could impact muscle function over the years. Hereby, we show that fat fraction along with muscle function tests can be considered a good outcome measures for clinical trials in LOPD patients.